The relation between sex, age, education level, and premedication towards lower-abdominal postoperative pain intensity at Sanglah General Hospital - Komang Alit Artha Wiguna; I Gusti Ngurah Mahaalit Aribawa; I Wayan Aryabiantara; Tjokorda Gde Agung Senapathi (Neurologico Spinale Medico Chirurgico, 2020)
Introduction: Pain reporting is very subjective. Several studies reveal sex, age, education level, and premedication have impacts on postoperative pain intensity. However, other studies report no relationship between these factors to pain intensity. There only a few researches on pain predictors in Bali, so this study conducts to determine relation between sex, age, education level, and premedication towards lower-abdominal postoperative pain intensity at Sanglah Hospital. Patients and Methods: This is an analytic cross-sectional study. The data were collected from medical records of patients after lower abdominal surgery at Sanglah Hospital from January to July 2018 and fit to inclusion criteria and did not suit to exclusion criteria. Data of patients characteristic were collected to indentify their relation toward pain intensity on the first day. Results: There were 99 patients post-lower abdominal surgery included in this study. The mean pain intensity based on sex was 2.83±0.87 for males and 2.98 ± 1.16 for females. Whereas based on ages were 3.04±1.11 for young, 2.90±0.95 for adults, and 2.40±0.96 for elderly. Based on the education level 2.40±1.26 in elementary educated patient, 2.72±1.27 in patients with junior high education, 2.96±1.04 in patients with high school education, and 3.15±0.74 in college patients. The average of pain in patients with premedication is 2.81±0.94 while the patient without premedication is 3.81±1.16. After performing correlation test, only the premedication factor showed a significant impact (p <0.05) to the pain intensity. Conclusion: Therefore, premedication has a greater impact than the other factor toward postoperative pain intensity at Sanglah Hospital.